PENGARUH KEHALUSAN SEMEN TERHADAP PENINGKATAN KEKUATAN MORTAR - Slat, Ventje Berty; Sumajouw, M. D.J; Wallah, S. E. (JURNAL ILMIAH MEDIA ENGINEERING, 2016)
AbstractSlurry density which is determined by the number of cavities / micro pores in the cement paste will reduce the strength to withstand loads on an element due to a reduction in the broad field of contact . Estrangement between aggregate and paste will causes micro cracks and result in crack propagation . Therefore, it is very important to reduce the number of pores in mortar and improve the hydration of cement more perfect . Effective method to overcome the problem of gap graded grainwhich serves as an adhesive as well as the use of granular cement filler is finer than standard cement The smaller cement granules will produce better hydration process .The aimed this study are to investigate the effect of fineness of cement in the mortar with a modified fineness method. The composition of the fineness of cement used are vary between 200 Standard , 400 , 500 and 600 m2 / kg . Specimens used have dimension of 50 × 50 × 50 mm and be tested at ages 3 , 7 , 14 and 28 days in order to get the compressive strength. In this study,ratio of cement to sand is 1 to 2.75 with water to cement ratio of 0.485. Type of cement used is the type of PCC ( Portland Composite Cement ) commonly used in IndonesiaResults indicate that the fineness of cement affects the mechanical properties of concrete and workability .Keywords:cement fineness , compressive strength . type of cement, mechanical properties, workabilityAbstrakKepadatan adukan ditentukan dengan banyaknya rongga/pori-pori mikro dalam pasta semen akan mengurangi kekuatan menahan beban pada suatu elemen karena terjadinya pengurangan luas bidang kontak. Kerenggangan antara agregat dan pasta menyebabkan terjadinya retak mikro dan mengakibatkan perambatan retak. Oleh karena itu menjadi sangat penting untuk mengurangi jumlah pori-pori pada mortar dan meningkatkan hidrasi semen yang lebih sempurna. Metode yang efektif mengatasi masalah kesenjangan gradasi butiran yang berfungsi sebagai perekat juga sebagai pengisi adalah penggunaan butiran semen yang lebih halus dari semen standar. Butiran semen yang lebih kecil akan menghasilkan proses hidrasi yang lebih baik.Penelitian ini bertujuan untuk menyelidiki pengaruh kehalusan semen pada mortar dengan metode modifikasi kehalusan. Komposisi kehalusan semen yang digunakan bervariasi antara 200, Standard, 400, 500 dan 600 m2/kg. Spesimen yang digunakan berukuran 50×50×50 mm dan diuji pada usia 3, 7, 14 dan 28 hari untuk mendapatkan nilai kuat tekan. Perbandingan semen dan pasir adalah 1 berbanding 2,75 dengan nilai faktor air semen 0.485 digunakan dalam penelitian ini. Jenis semen yang digunakan adalah tipe PCC (Portland Composite Cement) yang umum digunakan di Indonesia.Hasil menunjukkan bahwa kehalusan semen sangat berpengaruh terhadap sifat mekanis beton serta workability.Kata kunci : Kehalusan semen, kuat tekan. type semen, sifat mekanis, workability